Four Decades of Spatial-Temporal analysis of Seismicity Patterns in the Pinotepa Nacional region, Oaxaca, Mexico (GeoPatterns, 2025)
Contributing to the knowledge of the spatial distribution patterns involved in the most seismic regions of the world is an alternative way of anticipating the destructive consequences associated with significant earthquakes (>5.5Mw). This document provides evidence of the spatial aggregation patterns that are implicated in the spatial distribution of 32,046 seismic events from 1980 to 2021 period, in the Pinotepa Nacional region, Oaxaca, Mexico (Middle America Trench) and its relationship with intense local seismic activity and indirectly with possible hidden local unknown structures, settled some kilometers below the surface. Using GIS tools, to identify spatial patterns, the Local Indicators of Spatial Association analysis (LISA) and the Space–Univariate Local Moran's Index (SULMI) were applied. The analysis revealed that 21.0% of the epicenter’s spatial distribution is not random but tends to cluster toward seismicity potential zones. According to the LISA-SULMI approach applied, for each significant earthquake greater than 5.5Mw, a map of color intensities was obtained representing the degree of global spatial autocorrelation between the data. After a sequence of two significant earthquakes in 2018 (7.6 - 6.0 Mw), a hidden local tectonic feature 43 kilometers in diameter was revealed just 10 kilometers below the surface by micro-seismicity (2.0 and 2.9 Mw).
Keywords: Middle America Trench; Cocos Plate; LISA analysis; Moran's Index; spatial autocorrelation 1980-2021